Evolution, migration and clustering of helium-vacancy complexes in RAFM steel- depth resolved positron annihilation Doppler broadening study. Issue 22 (2nd August 2016) - Ramachandran, R.; David, C.; Rajaraman, R.; Panigrahi, B. K.; Amarendra, G.
Abstract: Indian Reduced Activation Ferritic Martensitic steel is implanted with 130 keV helium ions to a fluence of 5 × 10 14 and 1 × 10 16 ions/cm 2 and investigated using positron annihilation spectroscopy. The samples were characterised by defect sensitive S and W -parameters using depth resolved slow positron beam. A dose dependency is observed in the nucleation and growth of helium bubbles with annealing temperature. An experimental evidence for the migration of smaller helium-vacancy complexes is observed via the variation in thickness/width of irradiated layer with temperature. The S–W plot clearly shows the regions corresponding to defect annealing, bubble nucleation and growth.